Non-Hodgkins Lymphoma Presenting as a Skull Metastases: Case Report - Roka, Yam Bahadur; Roka, Narayani; Karki, Mohan (Eastern Green Neurosurgery, 2021)
The incidence of cerebral metastases has increased over the last few decades mainly due to the successful treatment of extra neural cancers and the prolonged survival of patients. The common causes of metastases are lung, kidney, breast and thyroid cancers. We present an interesting case of cerebral metastases that was managed as cerebral abscess, then as lung metastases before finally arriving to the correct diagnosis of Non-Hodgkin’s Lymphoma.